NURSING ASSISTANCE CONDUCTS IN THE FACE OF TRANSFUSION REACTIONS IN A UNIVERSITY HOSPITAL IN NATAL (Fiep Bulletin - online, 2013)
The practice of transfusion permeating the different stages in treating the patient, such as organ transplant, use of anticancer drugs and various surgical procedures, however, even a therapeutic procedure is common and frequent, the transfusion of blood products require special care in order to that risk is diminished, such as transfusion reactions, considering that some can be fatal. This study aims to assess the knowledge of the nursing team on the pipes taken care front of a transfusion reaction and the signs and symptoms of transfusion reaction. Descriptive study with prospective data and quantitative approach, conducted at Hospital Universitário Onofre Lopes (HUOL), located in the city of Natal / RN. The population was composed by 53 technicians from nursing and 1 nurse who participated in the training of care in general Hemotherapy in September 2008. Regarding the response of the people already on Tuesday witnessed a transfusion reaction only 16.7% say so. The answer about the signs and symptoms of transfusion reaction were rigors (68.5%), fever (48.1%), hypotension (42.6%), tachycardia (37.0%), hypertension (31.5% ), Nausea (27.8%), dyspnea (20.4%), urticaria (18.5%), cyanosis (16.7%) and pain (9.3%). Regarding the response on the pipes front of transfusion reactions, we observed that even described and placed in sequence as called for in haemovigilance Manual, the population of the study had doubts about this issue. This study shows that nursing professionals are having difficulty in identifying and linking the signs and symptoms of a transfusion reaction. The conduct of nursing care front of transfusion reactions are not always appropriate, ie there is not complying with the protocol established by the Ministry of Health
Keywords: signs and symptoms; blood transfusion; nursing